Attention-deficit/hyperactivity disorder in athletes - Leibold, C.; Smetana, R. M.; Statuta, S. M. (Clinics in Sports Medicine, 2024)
Attention-deficit/hyperactivity disorder (ADHD) is a relatively common neurodevelopmental disorder that, if not managed appropriately, can have profound negative influence on functioning in school, work, and relationships.